Physical Education Learning Management Using SHAPE’s OLPE and Peer-to-Peer Learning Concept to Hockey Skills of Secondary School Students - Chanpradit, Chatathorn; Samawathdana, Rungrawee (An Online Journal of Education, 2023)
This research aimed to study Physical education learning management using SHAPE’S OLPE and PEER-TO-PEER learning concept to Hockey skills of secondary school students. Methods: The subjects were 60 tenth grade students, divided into 15 students for the experimental group who were assigned to study under the physical education learning management system using SHAPE's OLPE and peer-to-peer learning concept, and 15 students in the control group who were assigned to study with the conventional teaching method. The research instruments were composed of eight physical education lesson plans using SHAPE's OLPE and the peer-to-peer learning concept with IOC 0.92, and the data collection instruments included a hockey skill test with IOC 1.00. The data were analyzed by mean, standard deviation, and t-test. The research findings were as follows: The mean scores of the practicing the right skills in hockey of the experimental group students after learning were significantly higher than before learning at .05 level., and the mean scores of the practicing the right skills in hockey of the experimental group students after learning were significantly higher than the control group at .05 level Physical education learning management using SHAPE’S OLPE and PEER-TO-PEER learning concept to Hockey skills of secondary school students were higher than Physical education learning management with the conventional teaching method.